Cytotoxicity Assay of Dètente Instantanée Côntrolée Pre-Dried Pandanus conoideus Lam. Extracts - Yunita, Oeke; Kohar, Indrajati; Allaf, Karim; Anggara, Aris Sri (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
Red fruit (Pandanus conoideus Lam.) contains antioxidant compounds in high levels, including beta-carotene and tocopherol, which neutralize free radical compounds which can cause cancer. Red fruit contains 46% water so red fruit can only last 5 days in this condition. To maintain its stability, it is necessary to dry it with various methods, for example détente instantanée contrôlée (DIC) is a revolutionary pressure drop drying procedure. Every procedure for drying raw material can affect its quality and activity, for example the anticancer activity of red fruit. In-vitro cytotoxicity of DIC pre-dried red fruit extracts on HeLa cells has never been tested, so it is important to study. Red fruit which was obtained from Klamono, Sorong, a highland in Papua was extracted with ethanol or hexane which previously dried by DIC pre-drying or conventional drying methods were weighed then dissolved in DMSO. Cytotoxicity assays was conducted using method the MTT with five levels of extract concentration. Result of this research showed that cytotoxicity assay of red fruit extracts on HeLa cells showed that red fruit extract can inhibit cell viability. The conventionally dried red fruit extract shows stronger cytotoxicity against HeLa cells than the DIC pre-dried extract. Red fruit extract cytotoxicity against HeLa cells: ethanolic extract of red fruit previously dried by conventional drying technique > ethanolic extract of red fruit previously dried by DIC pre-drying process > hexane extract of red fruit previously dried by conventional drying method > hexane extract of red fruit previously dried by DIC pre-drying process.